Aplikasi Probiotik Bacillus NP5 Bentuk Segar dan Mikrokapsul Untuk Pencegahan Infeksi Aeromonas hydrophilla Pada Ikan Mas (Cyprinus caprio) (Application of the Fresh Culture and Microencapsulated of Bacillus NP5 Probiotic to Prevent Aeromonas hydrophilla infection on Common Carp (Cyprinus carpio)) - Widanarni Widanarni; Alit Brilliant; Sukenda Sukenda (IPB University, 2014)
This study aimed to evaluate the effectiveness of fresh culture product and microencapsulated Bacillus NP5 for the growth performance and immune response of common carp infected by Aeromonas hydrophilla. The 5.09 ± 0.01g common carps were reared in aquarium and fed 3 times a day for 30 days. The dose of probiotic added to feed was 1%. The treatments in this study were positive and negative control (K+ and K-; without probiotic addition), the addition of fresh culture probiotic (A), and the addition of microencapsulated probiotic (B). Each treatment was repeated in 3 replications. On day 31, the fish of K+, A, and B were injected by 0.1mL (107cfu/mL) A. Hydrophilla. While the fish of K- were injected by phosphate buffer saline (PBS). The post-infection observation was carried out for 14 days. Treatment B showed the better results which were 96% survival rate, 2.66% of daily grown rate, 1.65 of feed conversion ratio, total bacteria in the intestine and immune response which were better than control.Keywords : Bacillus NP5, fresh culture, microencapsulated, Aeromonas hydrohilla, common carp